2013
DOI: 10.7133/jca.12-00028
|View full text |Cite
|
Sign up to set email alerts
|

A Ruptured Abdominal Aortic Aneurysm with a Left-sided Inferior Vena Cava

Abstract: An 81 year-old man had persistent lumbar pain, abdominal pain, and abdominal distension for a week was acutely admitted to our hospital. An enhanced computed tomography scan showed a ruptured infrarenal abdominal aortic aneurysm and a left-sided inferior vena cava. We successfully performed emergency abdominal aortic reconstruction, though we needed temporary abdominal closure with a vinyl sheet for 3 days for fear of abdominal compartment syndrome. He recovered uneventfully and was discharged 27 days after su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Lee et al [13] described a case of double left renal veins in the form of a venous collar in a 15-year-old girl who presented with intermittent haematuria. Nishibe et al [18] described the combination of abdominal aortic aneurysms and congenital anomalies of the IVC and its tributaries such as double IVC, left-sided IVC, circumaortic renal collar and retroaortic renal vein. In our case no.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [13] described a case of double left renal veins in the form of a venous collar in a 15-year-old girl who presented with intermittent haematuria. Nishibe et al [18] described the combination of abdominal aortic aneurysms and congenital anomalies of the IVC and its tributaries such as double IVC, left-sided IVC, circumaortic renal collar and retroaortic renal vein. In our case no.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, if we approach the AAA neck from the left of the Treitz ligament, as is often performed in cases of normal anatomy, the root of the mesentery and the crossing point of the LIVC would become obstacles to dissecting the AAA neck. We searched the literature for studies pertaining to AAA with LIVC, which described (or the author directly answered) the approach to the aneurysm; there was no restriction with regard to the date of publication (Table 1) [4][5][6][7][8][9][10][11][12]. We reviewed 9 case reports describing 10 open surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Holt et al (2007) suggested that IVC malformations may be part of a spectrum of retroperitoneal developmental anomalies that includes testicular descent and germ cell dysplasia. Although nine case reports identified an association between a left-sided IVC and AAA (Tsukamoto et al, 2000;Rispoli et al, 2001;Nishimoto et al, 2002;Papavassiliou et al, 2003;Giglia and Thompson, 2004;Nishibe et al, 2004;Evers et al, 2007;De Franciscis et al, 2008;Radermecker et al, 2008;Marin-Manzano et al, 2009), this probably reflects both publication bias and the fact that patients with an AAA routinely undergo abdominal CT imaging, thereby facilitating the discovery of any IVC anomaly. While the prevalence of left-sided IVC appears to be increased in some series of AAA patients (Hingorani and Ascher, 2003), the anomaly does not feature in other large series (Kaplan et al, 1999), suggesting that the two conditions are not genuinely linked.…”
Section: Discussionmentioning
confidence: 99%
“…Technical difficulties during abdominal surgery, particularly retroperitoneal surgery. The abnormal position of the IVC and/or its association with supernumerary renal veins and anomalous tributaries (Ito et al, 2007;Byler et al, 2009) complicate dissection and increase the risk of hemorrhage (Aljabri et al, 2001;Nishibe et al, 2004;Kumar et al, 2008). A transperitoneal rather than a retroperitoneal approach to the abdominal aorta and kidneys has been recommended in patients with a duplicate IVC to enable better visualization and control of aberrant vessels (Radermecker et al, 2008).…”
Section: Clinical Significancementioning
confidence: 99%
See 1 more Smart Citation